UV SPECTROPHOTOMETRY APPLICATION FOR QUANTITATIVE DETERMINATION OF VINPOCETINE IN DRUG FORMULATIONS - J. V. Monaykina; N. O. Nagorna; V. V. Nagorniy; S. O. Vasjuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Introduction. In this paper simple, rapid and sensitive assay methods for quantitative determination of vinpocetine in two new drug formulations (suppositories and nasal cream) are proposed. Analysis has been performed directly by using zero-order UV spectrophotometry. It is known from the special literature that the chromatographic techniques used for vinpocetine assay require expensive equipment and are rather time consuming. Therefore UV spectrophotometry is preferable due to its accuracy and simplicity.